PKM Pemanfaatan Canva untuk Presentasi di PT. Dwimitra Elektrindo - Dian Nazelliana; Purwanti Purwanti; Saputra Dwi Nurcahya; Sri Mardiyati (Abdi Jurnal Publikasi, 2023)
This research discusses training on the use of Canva's graphic design platform for presentations at PT. Dwimitra Elektrindo. The purpose of this research is to find out how far training on using Canva can improve employees' skills in making attractive and professional presentations. The method used is qualitative research with data collection techniques in the form of interviews and observations. The results of the research show that training on using Canva is very effective in improving employees' skills in making presentations. Employees can make better use of Canva's features, such as using the right templates, images and layouts so that the resulting presentations are more attractive and professional. In addition, employees can also better understand the applicable graphic design principles so that the resulting presentations are not only attractive, but also easily understood by the audience. Nonetheless, training on the use of Canva is only limited to providing an introduction and basic techniques, so further development is needed to increase the ability of employees to use Canva optimally. Keywords: Canva, presentation, training, employees, graphic design, qualitative.